FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI PUSKESMAS SEI PANCUR KOTA BATAM TAHUN 2017 - Nursamsi, Nursamsi; Nurul Aulia, Devy Lestari (Universitas Batam, 2019)
The high rate of infants mortality, particularly children age 1 to 5 years, 30% of it is reported to happen due lack of nutritional status. This study aims to analyze several potential factors influence the nutritional status of children. This research is an analytical survey study with cross sectional approach. The data was collected using questionnaires with anthropometrical measurement, in which the sample was taken by quota sampling technique. The study was conducted from June to July 2017 to 99 mothers of 1 to 5 year kids at Sei Pancur Health Centre of Batam. Further, the data then was analyzed using Chi Square statistical test. The result dismantles 81.8% mothers have good knowledge level on children nutritional status, besides, it is also found 54.5% mothers have low economic status, 39.4% have more than 2 children in family, and 65.7% get their children nutrition fulfilled. On the other hand, the Chi Square test issues the correlation of mother’s knowledge level with p=0.02, the economic status with p=0.03, and the number of kids owned with p= 0.02 to the nutritional status of their under-five years children. Therefore, it can be concluded that the factors like mothers’ knowledge level, number of newborns, as well as the economic status of the family contribute noticeable impacts to the children age 1 to 5 years nutritional status at Sei Pancur Health Centre of Batam City. At last, it is expected that the health centre personnel to routinely check the baby body weight as well as to give vitamins regularly as the nourishment needed for the children to grow.